RELATIONSHIP BETWEEN IN VITRO AND SEEDLING SELECTION FOR RESISTANCE TO SPOT BLOTCH (Bipolaris sorokiniana) IN WHEAT - CRISTALDO, ROSA MARIA DE LUJÁN OVIEDO (1997)
Twelve wheat (Triticum aestivum L.) genotypes were assessed, in vitro and in vivo, for resistance to spotblotch induced by Bipolaris sorokiniana, with the objective of verify correlation between calli and seedling responses. Toxicfiltrates were obtained from two fungai isolates and added to the culture mediam where the wheat callus developed; sporesuspensions were also produced and applied to wheat seedlings. The callus reaction was quantified by the difference betweengrowth of those exposed to the filtrates and the untreated cheks. The response of the seedlings was measured by the percentageof necrotic lesions present on the leaves. A smaller callus growth corresponded to a higher percentage of lesions on theseedling leaves.